A Review of Carbon-Based Materials for Safe Lithium Metal Anodes - Liu, Yan; Li, Xifei; Fan, Linlin; Li, Shufeng; Maleki Kheimeh Sari, Hirbod; Qin, Jian (Frontiers in Chemistry, 2019)
The lithium metal is a promising anode material with extremely high theoretical specific capacity (3860 mA h g-1), low density (0.59 g cm-3), and the lowest negative electrochemical potential (-3.04 V vs. the standard hydrogen electrode). However, uncontrollable Li dendrites growth leads to the short lifespan and catastrophic safety hazards, restricting its practical application over the past many years. With those challenges, some effective strategies have been adopted, including electrolyte modification, introducing a protective layer, nanostructured anodes, and membrane modification. The carbon-based materials have been demonstrated to obviously address the challenge of Li dendrites. In this review, the carbon-based materials were discussed in details for their application and challenges in lithium metal anodes protection. In addition, the applications of lithium anode with carbon-based materials were summarized for Li-S batteries and Li-O2 batteries.